Seed Geometry in Species of the Nepetoideae (Lamiaceae) - Diego Gutiérrez del Pozo; José Javier Martín-Gómez; Nick Israel Reyes Tomala; Ángel Tocino; Emilio Cervantes (Horticulturae)
The Nepetoideae are a subfamily of the Lamiaceae with 124 genera in three tribes: Elsholtzieae, Mentheae and Ocimeae. Their seeds have variable shapes, described in the literature by using adjectives derived from geometry, such as ellipsoid or elliptic, oblong, oval, ovate, ovoid, subspherical, round, spheroidal or their binary combinations. The articles describing seed shape mainly refer to single genera or even species, but a comprehensive approach covering different genera is lacking. Here we present general seed morphological measurements, curvature values and similarity to a geometric model (J-index) for seeds of the subfam. Nepetoideae. Seed morphology is described for 21 species belonging to nine genera of the three tribes and compared between genera as well as between different species in Mentha, Salvia, Thymus, Lavandula and Ocimum. The research objective was to investigate the application of the J-index and curvature analysis in the taxonomy of this subfamily. Individual genera can be defined by size and shape measurements, while species can be distinguished via the J-index and curvature. New methods are presented for studying the morphological relationships between taxa in the Nepetoideae.